Paratrichocladius nivalis (Goetgh.) described with observations on the taxonomic status of the species (Diptera Chironomidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Paratrichocladius nivalis (Goetgh.) was considered a junior synonym of P. skirwithensis (Edw.). The species is described from the lectotype and it is established as a valid species. The closely related species are described, the hypopygia are figured and a key to species belonging to the nivalis group is given.
Keywords: Paratrichocladius nivalis; P. skirwithensis; Chironomidae